Management and outcome of neonates with a prenatal diagnosis of esophageal atresia type A: A population‐based study. (28th May 2018) - Garabedian, C.; Bonnard, A.; Rousseau, V.; Sfeir, R.; ,; Drumez, E.; Michaud, L.; Gottrand, F.; Houfflin‐Debarge, V.
Abstract: Objective: Evaluate the neonatal management and outcomes of neonates with prenatal diagnosis of esophageal atresia (EA) type A. Methods: This population‐based study was conducted using data from the French National Register for infants with EA born from 2008 to 2014, including all cases of EA type A. We compared prenatal and neonatal characteristics and outcomes in children with prenatal diagnosis of EA type A with those with a postnatal diagnosis until the age of 1. Results: A total of 1118 live births with EA were recorded among which 88 (7.9%) were EA type A. Prenatal diagnoses were performed in 75 cases (85.2%), and counselling with a prenatal specialist was conducted in 84.8% of the prenatal group. Still within that group, the gestational age at delivery was significantly higher than in the postnatal group (36 [35‐38] versus 34 [32‐36] weeks; P = .048). Inborn births were more frequent in the prenatal group (86.1% vs 7.7%, P < .0001), and mortality and outcome were similar in both groups. Conclusion: Prenatal diagnosis is high in EA type A, which enables to offer an antenatal parental counseling and which avoids postnatal transfers. Prognosis of EA types A does not appear to be influenced by the prenatal diagnosis. Abstract : What is already known in this topic? The prenatal diagnosis of EA still remains a challenge. Esophageal atresia type A has the highest rate of prenatal diagnosis and a higher neonatal morbidity than EA type C. No studies so far have evaluated the impact of a prenatal diagnosis on the outcome of neonates with EA type A. What this study adds? The prenatal diagnosis rate is high for EA type A and usually leads to an antenatal parental counseling, to a better antenatal management, and it also helps avoiding postnatal transfers. The prognosis of EA type A does not appear to be influenced by any prenatal diagnosis.